Spain Brand. An institutional approach (Comillas Journal of International Relations, 2014)
The development of a “country-brand Project” proceeds from two paths: by the development of its methodological and doctrinal basis, or by the principal concepts in which lies a public strategy, focus on the upgrading of the international reputation and its consequences on the perceptions and decisions of the most influencers actors in the political and economical world landscape.A “country reputation” means the “prelude of a right decision” in the context of a global and changing communication impulse, where data, social relations and media coverage, determine a “brain system of values” and its “strengths or preferences”. The Spanish Economy has passed a period of important adjustments, with positive recognition of world leaders. The project, in terms of institutional design, must be the guarantor of public-private cooperation oriented to a foreign recognition of the country awareness, the components of the brand-values and the public support of initiatives related with that purpose. This text includes a brief resume of design, start-implement and short life period, where most Spaniards has been concerned.
Keywords: National Branding; Spain; Reputation; Values; Competitiveness